Lymph node fine-needle aspiration washout thyroglobulin in papillary thyroid cancer: Diagnostic value and the effect of thyroglobulin antibodies. (1st October 2016) - Konca Degertekin, Ceyla; Yalcin, Mehmet Muhittin; Cerit, Turgay; Ozkan, Cigdem; Kalan, Isilay; Iyidir, Ozlem Turhan; Altinova, Alev Eroglu; Akturk, Mujde; Toruner, Fusun; Akin, Murat; Cakir, Nuri
ABSTRACT: Purpose : Thyroglobulin (Tg) assessment in the needle washout after fine-needle aspiration biopsy (FNAB) of a suspicious neck lymph node (LN) is known to improve the diagnostic accuracy in patients with papillary thyroid cancer (PTC). However, there is still controversy on the best diagnostic cut-off levels for FNAB-Tg and whether thyroglobulin antibody (TgAb) positivity affects FNAB-Tg. The objectives of this study were to determine (i) the diagnostic power of different cut-offs for FNAB-Tg and (ii) if serum TgAb(+) negatively affects the FNAB-Tg evaluation.Methods : This was a retrospective cohort study analyzing PTC patients with suspicious neck LNs, in a university hospital setting, from October 2009 to October 2013. In total, 103 patients with PTC (226 LNs) undergoing ultrasound-guided FNAB for LNs were included. Cytology and FNAB-Tg levels were compared in reference to LN histopathology and the effect of TgAb(+) on FNAB-Tg levels was evaluated.Results : The diagnostic accuracies of FNAB-Tg cut-off of 1 and 10 ng/mL were 94.1% and 88.2%, respectively. Raising the cut-off from 1 to 10 ng/mL led to decreased sensitivity rates (91.9% vs. 83.9%). The receiver operating characteristic curve analysis demonstrated that the best FNAB-Tg cut-off was 1.2 ng/mL. There were no LNs with an FNAB-Tg ≥ 10 ng/mL that turned out to be cytologically or histopathologically benign. FNAB-Tg levels of the histopathologically malignant LNs were similar between TgAb (+) and TgAb (−) patients ( p = 0.546). Serum Tg predicted FNAB-Tg levels above 1 ng/mL ( p = 0.002) and FNAB-Tg predicted malignant histopathology ( p = 0.004), both independently of the TgAb status of the patient.Conclusions : FNAB-Tg ≥ 1 ng/mL has a superior diagnostic power, irrespective of TgAb (+), in PTC patients with suspected LN involvement.